2008
DOI: 10.1001/archpsyc.65.4.431
|View full text |Cite
|
Sign up to set email alerts
|

A Second Look at Prior Trauma and the Posttraumatic Stress Disorder Effects of Subsequent Trauma

Abstract: Prior trauma increases the risk of PTSD after a subsequent trauma only among persons who developed PTSD in response to the prior trauma. The findings suggest that preexisting susceptibility to a pathological response to stressors may account for the PTSD response to the prior trauma and the subsequent trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
188
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(223 citation statements)
references
References 59 publications
23
188
2
3
Order By: Relevance
“…The literature suggests that people with a history of prior trauma exposure are more likely than others to develop PTSD after exposure to subsequent traumas (Breslau, Peterson, & Shultz, 2008; Caramanica et al, 2015). Consistent with this evidence, a previous WMH report found that the vast majority of prior trauma types are significantly and positively associated with subsequent trauma exposure (Benjet et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The literature suggests that people with a history of prior trauma exposure are more likely than others to develop PTSD after exposure to subsequent traumas (Breslau, Peterson, & Shultz, 2008; Caramanica et al, 2015). Consistent with this evidence, a previous WMH report found that the vast majority of prior trauma types are significantly and positively associated with subsequent trauma exposure (Benjet et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…31 PTSD was more common in women at baseline, and given that both being female and having a prior episode of PTSD increases the risk of developing PTSD in response to a new traumatic event, higher rates of reexposure for women are likely to translate to much greater risk of PTSD in women injecting drug users. 6,9 Men and women were equally likely to report being physically assaulted or witnessing a physical assault, which translates to an exceptionally high rate of violence for women since community studies generally show that men are at considerably higher risk for violence than women. 32 Male and female injecting drug users may place themselves at increased risk for traumatic events via criminal activity and exposure to dangerous people and situations; 33,34 the higher rates of experiencing and witnessing physical assaults (compared to community samples) support this interpretation.…”
Section: Discussion High Rates Of Traumatic Event Re-exposurementioning
confidence: 99%
“…The few studies using general community-based samples show a 3-to 5-year re-exposure rate of 20-40%, with no gender differences. 6,7 The clinical relevance of these data is clear from studies that show that traumatic event reexposure alone or followed by PTSD increases the risk of further psychiatric impairment, including both PTSD and drug use. [6][7][8] There is good reason to believe that urban drug users experience a considerable amount of traumatic event re-exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the occurrence of different traumatic events exceeds the person's coping resources, although it is also possible that the susceptibility to respond to stressful or traumatic events with TI is also relevant. In this regard, research on the association between subsequent exposure to new traumatic events and the development of PTSD suggests that the susceptibility to respond pathologically to traumatic events (Breslau, Peterson, & Edward, 2010;Breslau, Peterson, & Schultz, 2008) and the frequency of these events (Cougle, Resnick, & Kilpatrick, 2009;Sledjeski, Speisman, & Dierker, 2010) are both important factors.…”
Section: Discussionmentioning
confidence: 99%